华兹华斯自然文本的符号学阐释. - 杨依依 (Foreign Literature Studies, 2023)
The nature in Wordsworth's poetry is culturally-loaded, but it can also be textualized. The units of meaning formulated in the interplay between nature and culture can be called Nature-Text. Nature-Text refers to the natural environment and literary writing itself as well. In this sense, nature is not only an extension of human consciousness or a tool for expressing feelings, but also an independent and self-sufficient existence. In other words, it is both a subject with symbolic potential and a dynamic participant in the process of literary writing. Therefore, Wordsworth's portrayal and description of nature can also be perceived as an artistic performance of "transcoding," aiming at restoring the two-way communication between nature and the cultural signs of humankind. Different from the traditional concept of Romantic poetics, this two-way communication can be interpreted from a semiotic perspective as a process where the poet adopts natural and intuitive thinking to complete the versification of Nature-Text.